Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1002/ijc.24447
|View full text |Cite
|
Sign up to set email alerts
|

A prospective analysis of the association between macronutrient intake and renal cell carcinoma in the European Prospective Investigation into Cancer and Nutrition

Abstract: Previous case‐control studies have suggested that a high intake of animal foods and its associated nutrients are associated with an increased risk of renal cell carcinoma, although data from prospective studies are limited. We report here on the relationship between macronutrient intake and renal cell carcinoma incidence among 435,293 participants enrolled in the European Prospective Investigation into Cancer and Nutrition. Cox proportional hazard models were used to examine the association of dietary intake o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
7

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 24 publications
2
11
0
7
Order By: Relevance
“…No significant associations were found between intake of total fat, SFA, MUFA, or PUFA and renal cell cancer. Similarly, no significant associations were found for intake of total fat, SFA, MUFA, or PUFA in the EPIC-study with a mean follow-up of 8.8 years reported by Allen et al (171). …”
Section: Resultsmentioning
confidence: 50%
See 1 more Smart Citation
“…No significant associations were found between intake of total fat, SFA, MUFA, or PUFA and renal cell cancer. Similarly, no significant associations were found for intake of total fat, SFA, MUFA, or PUFA in the EPIC-study with a mean follow-up of 8.8 years reported by Allen et al (171). …”
Section: Resultsmentioning
confidence: 50%
“…Two articles reported results from 14 PCS (171, 172). The article by Lee et al (172) comprises results from a pooled analysis of 13 PCS from Australia, Canada, Finland, Netherlands, Sweden, and the United States with follow-ups between 7 and 20 years.…”
Section: Resultsmentioning
confidence: 99%
“…Over the past 2 decades, the association between fiber intake and RCC risk has been reported in one other prospective cohort (34) and in a handful of case-control studies (35)(36)(37)(38)(39). In the 2 largest studies, no association was observed in the European Prospective Investigation into Cancer (34), whereas total dietary fiber intake was inversely related to RCC risk in a large Canadian population-based case-control study (35).…”
Section: Discussionmentioning
confidence: 99%
“…Dietary fiber is rich in fruit and vegetables. Some studies [12, 40], although not all [23, 25, 41], have found that high intake of fiber may lower the risk of RCC development.…”
Section: Discussionmentioning
confidence: 99%